1995
DOI: 10.1080/00288233.1995.9513098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of harvest and paclobutrazol on seed yield in white clover cv. Grasslands Pitau

Abstract: Maximum potential harvestable and actual seed yield of white clover (Trifolium repens L.) cv. Grasslands Pitau following a mid November closing at Palmerston North, New Zealand, was obtained at a harvest 25 days after peak flowering. Seed yield did not differ significantly when harvest was delayed from 25 to 35 days after peak flowering, but was significantly lower with harvests at 40 and 45 days after peak flowering. This response to time of harvest was not altered by applying the growth retardant paclobutraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Silberstein et al (1996) further reported a decrease in stem height and the mean number and length of internodes from PGR application; however, Niemelainen (1987) ascribed the increase in yield to better seed set, not morphological changes associated with decreased cell division. Silberstein et al (1996) and Budhianto et al (1995), working with red clover and white clover ( T. repens L.), respectively, reported an increase in the number of inflorescences stem −1 and inflorescences m −2 . In white clover, Budhianto et al (1994) showed an increase in seed yield potential with paclobutrazol [ 2RS,3RS ‐1‐(4‐chlorophenyl)‐4,4‐dimethyl‐d‐(1 H ‐1,2,4‐triazol‐1‐yl) pentan‐3‐ol] application through an increase in inflorescences m −2 ; however, no actual seed yield increase was measured.…”
mentioning
confidence: 99%
“…Silberstein et al (1996) further reported a decrease in stem height and the mean number and length of internodes from PGR application; however, Niemelainen (1987) ascribed the increase in yield to better seed set, not morphological changes associated with decreased cell division. Silberstein et al (1996) and Budhianto et al (1995), working with red clover and white clover ( T. repens L.), respectively, reported an increase in the number of inflorescences stem −1 and inflorescences m −2 . In white clover, Budhianto et al (1994) showed an increase in seed yield potential with paclobutrazol [ 2RS,3RS ‐1‐(4‐chlorophenyl)‐4,4‐dimethyl‐d‐(1 H ‐1,2,4‐triazol‐1‐yl) pentan‐3‐ol] application through an increase in inflorescences m −2 ; however, no actual seed yield increase was measured.…”
mentioning
confidence: 99%
“…a similar result of increasing seed yield for oats was achieved by pirjo & ari (2003), where chlormequat applied at the elongation stage of oat suppressed stem growth and accelerated tiller growth and the number of racemes per shoot. Budhianto et al (1995) reported that paclobutrazol significantly increased inflorescence number of white clover (Trifolium repens L.) at peak flowering stage.…”
Section: Introductionmentioning
confidence: 99%